Cell motility : from molecules to organisms - Ridley, Anne; Peckham, Michelle; Clark, Peter, 1956- (Wiley, 2004)
Recent advances in molecular and biophysical techniques, particularly fluorescence and live cell imaging, are revolutionizing the study of cell motility. New bioprobes not only reveal simple intracellular localization, but also contain details of post-translational modifications, conformational state and protein-protein interactions.